32.7k views
0 votes
Question in image down below

Question in image down below-example-1

2 Answers

2 votes

Answer:

x = -4

Explanation:

3x - 2(3x - 2) = 16

3x - 6x + 4 = 16

-3x + 4 - 4 = 16 - 4

-3x = 12

(-3x)/(-1/3) = 12/(-1/3)

x = -4

User BkSouX
by
4.7k points
4 votes

Answer:


{ \tt{3x - 2(3x - 2) = 16}} \\ { \tt{3x - 6x + 4 = 16}} \\ { \tt{ - 3x = 12}} \\ { \tt{x = - 4}}

Checking solution....!


{ \tt{ 3x - 2(3x - 2) = 16}} \\ { \tt{3( - 4) - 2(3 * - 4 - 2) = 16}} \\ { \tt{ - 12 + 28 = 16}} \\ { \tt{16 = 16}}

Since L.H.S = R.H.S, the solution is consistent

User Aatif Bandey
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.